2008
DOI: 10.1038/sj.bjc.6604766
|View full text |Cite
|
Sign up to set email alerts
|

Parental attitudes and information needs in an adolescent HPV vaccination programme

Abstract: We sent a questionnaire to 38% (1084) of 2817 parents whose daughters had been offered human papillomavirus vaccination and who had agreed to participate. Of these, 60% (651) returned a questionnaire. Responses suggested that fact sheets and parent information evenings confirmed, rather than changed, consent decisions. The views of active refusers on safety and efficacy may be difficult to change, lowering vaccine coverage. British Journal of Cancer (2008Cancer ( ) 99, 1908Cancer ( -1911 In the United Kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
33
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 19 publications
4
33
0
1
Order By: Relevance
“…The proportion of parents we found who held this belief is consistent with previous studies where estimates ranged from 6–12% before HPV vaccine licensure and as high as about 30% in more recent studies 2 19 20 25 27. Taken together, these estimates suggest some variability in sexual disinhibition beliefs and that they may be changing over time.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The proportion of parents we found who held this belief is consistent with previous studies where estimates ranged from 6–12% before HPV vaccine licensure and as high as about 30% in more recent studies 2 19 20 25 27. Taken together, these estimates suggest some variability in sexual disinhibition beliefs and that they may be changing over time.…”
Section: Discussionsupporting
confidence: 90%
“…Belief that regular Pap smears are unnecessary after HPV vaccination was infrequent. This is consistent with past research showing that most adult women and parents recognised the need for Pap smear screening after HPV vaccination 25 26. However, belief that Pap smears may safely be stopped was somewhat more common among male parents and those from minority racial and ethnic groups.…”
Section: Discussionsupporting
confidence: 89%
“…This finding corroborates a number of studies conducted before vaccine marketing that suggested that parental concerns about behaviors such as earlier age at sexual debut or less attention to safe sex were associated with lower rates of vaccine intentions (22,23). The proportion of parents reporting concerns about sexual disinhibition varies considerably across studies, with low levels of concerns in some (19,24) and high levels (25-30%) in others (25,26). In this population-based sample, 22% agreed or strongly agreed that "vaccinating my daughter would send a message that it is okay to have sex.…”
Section: Discussionsupporting
confidence: 75%
“…외국의 선행연구결과 HPV 백신접종에 대한 어머니들의 수 용도는 전반적으로 긍정적이었는데 (Khan et al, 2008;Marlow, Waller, & Wardle, 2008;Olshen, Woods, Austin, Luskin, & Bauchner, 2005;Stretch et al, 2008;Walsh et al, 2008) (Peres, 2010), 이와 같은 경제적 부 담으로 인하여 외국에서도 대상자의 70.5%가 무료 백신접 종을 원하였고 (Walsh et al, 2008), 84%의 어머니들이 무료 백신이라면 자녀에게 접종할 것이라고 보고하였다 (Fazekas et al, 2008). 국내에서도 HPV 백신은 기관마다 차이는 있 지만 4가 백신의 경우 50~60만원 수준으로 국내 시판되는 백신중에서 가장 비싸기 때문에, 백신접종 권장에 대한 경 제성 논란도 제기되고 있는 실정이다 (Yoo, 2010) Yoo, 2010 (Lee & Park, 2011;Reiter, Brewer, Gottlieb, McRee, & Smith, 2009;Stretch et al, 2008;Tissot et al, 2007), 백신 이 성적 활동을 일찍 촉진할 수 있다는 걱정 (Bartolini et al, 2010)과 HPV에 대한 정보와 백신의 필요성 (Fazekas et al, 2008)이 제시되었다. 그 외로 어머니의 과거 생식기 사마귀 또는 HPV 감염력 (Dempsey et al, 2006), Pap 검사결과 (Mays, Strum, & Zimet, 2004), 어머니의 HPV 백신접종 (Brewer & Fazekas, 2007) (Table 1).…”
unclassified